Detection parasites of Indian Mackerel (Rastrelliger kanagurta) in North Sumatera, Indonesia - Eri Yusni; Luvi Syafrida Handayani (Depik, 2022)
The purpose of this study was to identify ectoparasites and their prevalence infecting Rastrelliger kanagurta in North Sumatera, Medan. So far, people use this fish as a processed product. The method used in this study is a survey method with direct collection at the research site. Samples were taken using random sampling technique. Sampling was carried out in five places in Belawan with the number of samples studied as many as 30 individuals with an average length of 25.3 cm and a weight of 193.7 grams. Identification was carried out in a laboratory using a light microscope at the Faculty of Agriculture, University of North Sumatra. The results of this study found seven types of parasites that infect the surface in the muscles, fins and gills. The parasites found in their respective prevalence were infected Dactylogyrus sp. 13.33% was found in muscus, Austrobdella sp. 30% found in fin. While the parasites found in the gills were Zoothamnium sp as much as 6.67%, Diphyllobothrium sp as much as 16.67%, Rhadinorynchus sp. 53.33%, Camallanus sp. 20% and Anisakis sp. 3.33%. Rhadinorynchus sp. is the parasite with the highest prevalence rate, found on the scales, gills and fins respectively of mackerel.